2020
DOI: 10.13106/jafeb.2020.vol7.no4.21
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Liquidity Risks on the Relationship between Earnings and Stock Return on Jordanian Public Shareholding Industrial Companies

Abstract: The objectives of this study are threefold: 1) to identify the concepts of earnings, stock return and liquidity risks on public shareholding industrial companies listed in the Amman Stock Exchange, 2) to investigate the relationship between earnings, stock return, strength and direction of this relationship, and 3) to find out the effect of liquidity risks at stock return and the effect of liquidity risks on the relationship between earnings and stock return on Jordanian public shareholding industrial companie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…On the Australian stock market, Marshall and Young (2003) found a statistically significant negative relationship between stock return and the liquidity (turnover rate). Shakatreh (2020) examined the effect of liquidity risks at a stock return on the Amman Stock Exchange by 52 industrial companies over the period 2014-2019. The result shown that there is a statistically significant negative effect of liquidity risk on stock return.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the Australian stock market, Marshall and Young (2003) found a statistically significant negative relationship between stock return and the liquidity (turnover rate). Shakatreh (2020) examined the effect of liquidity risks at a stock return on the Amman Stock Exchange by 52 industrial companies over the period 2014-2019. The result shown that there is a statistically significant negative effect of liquidity risk on stock return.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors found a remarkable level of diversity in the intended scope of these indicators, ranging from well-known indicators that deal with liquidity levels and capital structure such as a firm's Liquidity Ratio and a bank's capital to asset ratio, to less widely used indicators that deal with external factors such as FDI, unemployment rate and the realization of the financial crisis variable, which intends to simulate for the moment a financial crisis was first detected. Shakatreh (2020) research aimed to deconstruct the concepts of earning, stock return and liquidity risk, following up with a thorough review of the available literature, intending to scale the order of importance of these various indicators and their relative bearing on stock market performance. Finally, the author sought to examine the nature and strength of the relationship between these variables.…”
Section: Introductionmentioning
confidence: 99%